MENGUNGKAP MAKNA DAN TUJUAN JIHAD DALAM SYARIAT ISLAM - Farid Naya (TAHKIM, 2017)
Jihad is one of the few languages that has always been interesting and actual issue from classical times to the contemporary era. In fact, sometimes, jihad misunderstood and prone to distortion of meaning, so meaning of positive turn into negative meanings, and tend to be extreme. For example, jihad connoted with terrorists and justifying terrorism. The phenomenon of distortion of the meaning of jihad, mainly due to lack of understanding of the meaning and purpose of jihad Teron itself. Therefore, it is urgent to assess and explore the meaning and purpose of jihad in Islamic law. Keywords: jihad, islamic law